1989
DOI: 10.1002/1097-0142(19890101)63:1<126::aid-cncr2820630120>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic findings and prognosis in neuroblastoma with emphasis on marker chromosome 1

Abstract: The relationship between cytogenetic findings and prognosis in 51 pediatric patients with neuroblastoma is described. Patients were classified into the following four groups based on karyotypic findings: (1) near diploidy, 42 to 47 chromosomes (n = 11); (2) hyperdiploidy, 50 to 56 chromosomes (n = 4); (3) near triploidy, 60 to 77 chromosomes (n = 33); and (4) hypotetraploidy, 80 to 83 chromosomes (n = 3). Patients with near diploid or hypotetraploid karyotypes also had several structural abnormalities includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(57 citation statements)
references
References 30 publications
4
53
0
Order By: Relevance
“…Cytogenetic studies have suggested that deletion of the short arm of chromosome 1 (1p) occurs frequently in NB (Brodeur and Fong, 1981;Hayashi et al, 1989), and is associated with a poor prognosis (Hayasi et al, 1989;Brodeur et al, 1989;Caron et al, 1996). Molecular genetic studies have revealed several speci®c alterations in NB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytogenetic studies have suggested that deletion of the short arm of chromosome 1 (1p) occurs frequently in NB (Brodeur and Fong, 1981;Hayashi et al, 1989), and is associated with a poor prognosis (Hayasi et al, 1989;Brodeur et al, 1989;Caron et al, 1996). Molecular genetic studies have revealed several speci®c alterations in NB.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular genetic studies have revealed several speci®c alterations in NB. One of these is ampli®cation of the MYCN gene that is associated with a poor prognosis in NB (Seeger et al, 1985;Hayashi et al, 1989;Brodeur and Fong, 1989). Another is the loss of heterozygosity (LOH) at the 1p (Fong et al, , 1992Takita et al, 1995;Schwab et al, 1996), long arm of chromosome 11 (11q) (Srivatsan et al, 1993) and 14q (Srivatsan et al, 1993;Suzuki et al, 1989) in NB.…”
Section: Introductionmentioning
confidence: 99%
“…At diagnosis, nearly 50% of neuroblastomas are metastatic, mainly to the bone marrow. Several biological tumour parameters such as N-myc gene amplification (Brodeur et al, 1984), loss of heterozygosity of chromosome lp (Fong et al, 1989;Hayashi et al, 1989), diploidy (Hayashi et al, 1989) and mdrl gene overexpression (Bourhis et al, 1989;Chan et al, 1991) have been identified as strong predictors of a poor outcome. Despite the use of intensive chemotherapy protocols, including high-dose chemotherapy followed by autologous bone marrow stem cell support, the survival of children treated for non-metastatic neuroblastoma with Nmyc amplification or for metastatic neuroblastoma (over 1 year of age) remains poor.…”
mentioning
confidence: 99%
“…Both N-myc amplification (Brodeur, 1990a;Brodeur et al, 1984;Bourhis et al, 1991;Seeger et al, 1985) and deletion of chromosome lp (as detected by cytogenetic analysis) (Christiansen and Lampert, 1988;Hayashi et al, 1989;Kaneko et al, 1987) appear strongly correlated with a poor clinical outcome and with each other, but it is not yet clear if they are independent prognostic variables. Nevertheless, they appear to characterize a genetically distinct subset of very aggressive neuroblastomas.…”
Section: Kb-mentioning
confidence: 99%